Trends in contraceptive prevalence rates in sub-Saharan Africa since the 2012 London Summit on Family Planning: results from repeated cross-sectional surveys. Issue 7 (July 2019) - Ahmed, Saifuddin; Choi, Yoonjoung; Rimon, Jose G; Alzouma, Souleymane; Gichangi, Peter; Guiella, Georges; Kayembe, Patrick; Kibira, Simon P; Makumbi, Fredrick; OlaOlorun, Funmilola; Omoluabi, Elizabeth; Otupiri, Easmon; et al.
Summary: Background: The Family Planning 2020 (FP2020) initiative, launched at the 2012 London Summit on Family Planning, aims to enable 120 million additional women to use modern contraceptive methods by 2020 in the world's 69 poorest countries. It will require almost doubling the pre-2012 annual growth rate of modern contraceptive prevalence rates from an estimated 0·7 to 1·4 percentage points to achieve the goal. We examined the post-Summit trends in modern contraceptive prevalence rates in nine settings in eight sub-Saharan African countries (Burkina Faso; Kinshasa, DR Congo; Ethiopia; Ghana; Kenya; Niamey, Niger; Kaduna, Nigeria; Lagos, Nigeria; and Uganda). These settings represent almost 73% of the population of the 18 initial FP2020 commitment countries in the region. Methods: We used data from 45 rounds of the Performance Monitoring and Accountability 2020 (PMA2020) surveys, which were all undertaken after 2012, to ascertain the trends in modern contraceptive prevalence rates among all women aged 15–49 years and all similarly aged women who were married or cohabitating. The analyses were done at the national level in five countries (Burkina Faso, Ethiopia, Ghana, Kenya, and Uganda) and in selected high populous regions for three countries (DR Congo, Niger, and Nigeria). We included the following as modern contraceptive methods: oral pills, intrauterine devices, injectables, male and female sterilisations, implants, condom, lactational amenorrhea method, vaginal barrier methods, emergency contraception, and standard days method. We fitted design-based linear and quadratic logistic regression models and estimated the annual rate of changes in modern contraceptive prevalence rates for each country setting from the average marginal effects of the fitted models (expressed in absolute percentage points). Additionally, we did a random-effects meta-analysis to summarise the overall results for the PMA2020 countries. Findings: The annual rates of changes in modern contraceptive prevalence rates among all women of reproductive age (15–49 years) varied from as low as 0·77 percentage points (95% CI −0·73 to 2·28) in Lagos, Nigeria, to 3·64 percentage points (2·81 to 4·47) in Ghana, according to the quadratic model. The rate of change was also high (>1·4 percentage points) in Burkina Faso, Kinshasa (DR Congo), Kaduna (Nigeria), and Uganda. Although contraceptive use was rising rapidly in Ethiopia during the pre-Summit period, our results suggested that the yearly growth rate stalled recently (0·92 percentage points, 95% CI −0·23 to 2·07) according to the linear model. From the meta-analysis, the overall weighted average annual rate of change in modern contraceptive prevalence rates in all women across all nine settings was 1·92 percentage points (95% CI 1·14 to 2·70). Among married or cohabitating women, the annual rates of change were higher in most settings, and the overall weighted average was 2·25 percentage points (95% CI 1·37–3·13). Interpretations: Overall, the annual growth rates exceeded the 1·4 percentage points needed to achieve the FP2020 goal of 120 million additional users of modern contraceptives by 2020 in the select study settings. Local programme experiences can be studied for lessons to be shared with other countries aiming to respond to unmet demands for family planning. The findings of this study have implications for the way progress is tracked toward achieving the FP2020 goal. Funding: The Bill & Melinda Gates Foundation.